ANALISIS PERUBAHAN KRITERIA PERATURAN BAPEPAM LK NOMOR II.K.1 TENTANG KRITERIA DAN PENERBITAN DAFTAR EFEK SYARIAH TAHUN 2007, 2009, 2012 - A Abdussalam; Neni Nuraeni (Department of Sharia Economic Law, Faculty Sharia and Law, UIN Sunan Gunung Djati Bandung, 2019)
ABSTRACTThis research is motivated by regulations concerning criteria qualitative, namely the type of business and quantitative criteria, namely the ratio Islamic stock finance published in 2007, 2009 and 2012 in the form Bapepam and LK regulations. In Bapepam and LK regulations Number II.K.1 about Criteria and Issuance of List of Sharia Securities there is still tolerance to financial ratios, namely to interest-based debt with income interest based and other non-halal income. In the formulation of this study is how the changes, reasons and position of the Bapepam LK Regulation Number II.K.1 concerning Criteria and Issuance of List of Sharia Securities. This study aims (1) To find out changes in Qualitative Criteria and Quantitative Criteria in Bapepam LK Regulation Number II.K.1 about Criteria and Issuance of List of Sharia Securities in 2007, 2009, 2012. (2) For find out what is the reason for the changes in Bapepam LK regulations number II.K.1 about Criteria and Issuance of Sharia Securities List in 2007, 2009 and 2012. (3) To determine the Position of Bapepam LK Regulation Number II.K.1 about Criteria and Issuance of List of Sharia Securities in the legal system Capital Market in Indonesia. This research was conducted by juridical-normative method, namely analyze the contents of legislation in the form of Bapepam and Regulations LK. The source of the research is Bapepam LK Regulation Number II.K.1 and Fatwa DSN-MUI. Techniques for collecting data through interviews, documentation studies and literature review. Qualitative data analysis by collecting data to then be interpreted and conclusions taken. This study concludes (1) changes in 2007 to 2009 occur changes to qualitative and quantitative criteria but not too significant. Then in 2009 to 2012 there was a change in quantitative criteria that is to financial ratios to point (a) interest-based debt ratios at appeal with total assets of not more than 45%. (2) the reason that happened to changes from 2007 to 2009 were to provide information comprehensive about sharia securities, while changes from 2009 to 2012 are because the ratio calculation based on capital is considered irrelevant reasons: (i) Companies that lose (small capital) are not necessarily performance going forward is not good; (ii) No other country uses that ratio capital-based. (3) Bapepam LK Regulation Number II.K.1 concerning Criteria and The issuance of the List of Sharia Securities is still valid and provides reference to issuers that enter the List of Sharia Securities. Even though it is currently Bapepam LK has been abolished and merged with Bank Indonesia to become a Service Authority Finance (OJK). Because there are no new regulations issued by the FSA and Bank Indonesia, so that this regulation is still valid.